Yeast Ssu72 Protein as a Mediator of Gene Loop Formation at Bidirectional Promoters - Lopez, Kevin Jose; Henderson, Jeffrey Odell (Journal of Student Research, 2015)
Research over the past ten years has revealed that bidirectional promoters are a common feature of eukaryotes from yeast to metazoans. Gene loops are three-dimensional structures that inhibit divergent transcription at bidirectional promoters. Ssu72, a multifunctional protein phosphatase, has been identified as a key component in directing gene loop formation. Molecular genetic characterization first identified Ssu72 as a component of the transcription initiation complex through an interaction with TFIIB. More recently, Ssu72 has been shown to inhibit divergent transcription by simultaneously binding to both promoter and terminator elements. Here, we describe the path of Ssu72 research from its discovery as a transcriptional regulatory protein to its role in the maintenance of transcriptional memory and repression of noncoding RNAs (ncRNAs). Finally, we consider the role of Ssu72 and gene loops in human health.